Hydrogen Valleys – Energy transition and local development scenarios for medium-sized cities - Alessandra Battisti; Angela Calvano (Agathón)
In the current decarbonisation scenario, production, transport and energy consumption affect the territorial dimension of communities, while the proximity character of renewable sources and distributed generation systems make it possible to redefine the socio-spatial link with energy. This involves deterritorialisation by decommissioning fossil fuel systems, re-territorialization by converting brownfield sites and constructing a value chain based on climate neutrality. The project of territorial heritage regeneration, reinterpreted by settled communities as a potential energy network, meets the needs of the New Deal by guaranteeing secure and equitable energy. The paper aims to understand how medium-sized cities can contribute to the experimentation of decision-making processes and hydrogen design solutions.